2017
DOI: 10.3399/bjgp17x693125
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to allied health professionals through the Champlain BASEeConsult service: a cross-sectional study in Canada

Abstract: The eConsult service has demonstrated the ability to support prompt communication between PCPs and AHPs, improving patients' access to AHP care. Given the importance of AHPs in providing primary care, allied health services should be offered in the menu of specialties available through electronic consultation services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…At the time of our 2015 review, most studies reported high PCP satisfaction with e-consults, including perceived value, improved timeliness of specialty input, and enhanced communication with specialist. Newer studies using PCP surveys support these findings, 11,13,14,[18][19][20][21][22]24,26,[29][30][31][33][34][35][36]41,54,57,60,[62][63][64][65][67][68][69][70][71] and 2 qualitative studies also report generally high PCP satisfaction. 7,39 More recent studies have also described a strong educational benefit to less-experienced PCPs.…”
Section: Patient and Clinician Experiencementioning
confidence: 85%
See 1 more Smart Citation
“…At the time of our 2015 review, most studies reported high PCP satisfaction with e-consults, including perceived value, improved timeliness of specialty input, and enhanced communication with specialist. Newer studies using PCP surveys support these findings, 11,13,14,[18][19][20][21][22]24,26,[29][30][31][33][34][35][36]41,54,57,60,[62][63][64][65][67][68][69][70][71] and 2 qualitative studies also report generally high PCP satisfaction. 7,39 More recent studies have also described a strong educational benefit to less-experienced PCPs.…”
Section: Patient and Clinician Experiencementioning
confidence: 85%
“…62 Several publications from the Champlain BASE program report on a PCP survey question at the end of each e-consult request about whether a face-to-face consult would have been sent in the absence of the e-consult option. Depending on specialty of the consultation being requested, 32%-80% of PCPs report that a face-to-face visit would have been required absent the e-consult, [12][13][14]16,[18][19][20][21]24,26,[28][29][30][31][32][33][34][35][36]41,47,51,58,62,65 suggesting that up to as many as 4 out of 5 e-consults are perceived to obviate a face-to-face visit. Using these data on face-to-face referrals avoided, the Champlain BASE group calculated payer costs decreasing from $131.05 to $6.45 (CAD) per econsult from year 1 to year 3 of the program.…”
Section: Costsmentioning
confidence: 99%
“…Other benefits of virtual consultations may be to offer new opportunities to extend service provision to a broader variety of service user groups and clinical settings, 33 provide shared learning opportunities 19 and greater joint working across professional groups, including allied health professionals (physiotherapists, pharmacists) and settings, [34][35][36][37][38] and possibly reducing the number of referrals to specialists. 39 Virtual consultations might also become the new medium for general practitioners (GPs) to use in their additional training roles.…”
Section: Clinicians/workforcementioning
confidence: 99%
“…We screened 181 full-text articles, of which we excluded 108 records after applying exclusion criteria. A total of 72 studies were eligible for data extraction (Figure).…”
Section: Resultsmentioning
confidence: 99%